P031 Adherence with Methotrexate in Tunisian Juvenile Idiopathic Arthritis Patients. (11th November 2021) - Bettaieb, Hiba; Triki, Wafa; Maatallah, Kaouther; Ferjani, Hanene; Ben Nessib, Dorra; Kaffel, Dhia; Hamdi, Wafa
Abstract: Background: Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in the pediatric population. Methotrexate (MTX) has been considered as the cornerstone of treatment of poly and oligoarticular subtypes of JIA. However, this treatment is supposed to be for long term, which may involve an obstacle for adherence. The aims of the study were to evaluate adherence of Tunisian JIA patients to MTX and to identify factors associated with high adherence to MTX. Methods: A cross-sectional study including patients with confirmed JIA diagnosis, according to the International League of Associations for Rheumatology (ILAR) criteria, was performed. Demographic data as well as disease characteristics were obtained from medical records. Laboratory markers including erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were collected. Adherence was measured, for patients under MTX for >3 months, using the 5-item Compliance Questionnaire Rheumatology (CQR5) (1). Patients were divided into two groups: group 1: High adherence (HA) for patients having a CQR5 ≥ 80% and group 2: low adherence (LA) for patients having CQR5 < 80%. A p inferior to 0.05 was considered statistically significant. Results: The study included 29 patients (10 males and 19 females) with a mean age at disease onset of 9.1 ± 3.4 years. The mean disease duration was 61 ± 79 months [7–336]. JIA subtypes were in decreasing order of frequency as follows: enthesitis-related arthritis ( n = 13), oligoarticular ( n = 8), Polyarticular without rheumatoid factor ( n = 4), Polyarticular with rheumatoid factor ( n = 2), systemic ( n = 1) and, psoriatic arthritis ( n = 1). A biologic inflammatory syndrome was found in 48.3% ( n = 14) of cases. The mean ESR and CRP were 20 mm/h ± 11.3 [3–98] and 5 ± 17.8 mg/l [0–56] respectively. Nineteen (65.5%) patients had coxitis. Overall, 55.17% of patients ( n = 16) were treated with MTX with a mean weekly dose of 9.2 ± 3.2 mg [5–15]. MTX was orally administrated in all patients. NSAIDs and prednisone were prescribed in 51.7% ( n = 15) and 17.2% ( n = 5) of cases respectively. The MTX was associated with biological DMARDs in five patients (17.2%). It was about Etanercept in 4 patients and Tocilizumab in 1 patient. Mean CQR5 score was 70.8% ± 18 [25–100]. Only seven patients (43.8%) showed high adherence to MTX. The statistical study revealed no difference between HA and LA in term of gender ( P = 0.84), age at disease onset ( P = 0.39), disease duration ( P = 0.9), prednisone use ( P = 0.22), the occurrence of coxitis ( P = 0.2), ESR ( P = 0.83) and CRP ( P = 0.033) rates. Conclusion: In this study, less than one half of JIA patients were highly adherent to MTX according to CQR5. Low adherence should be considered before declaring MTX treatment failure.